Strategi Pemasaran BMT Al Makmur dalam Meningkatkan Jumlah Nasabah Fundig dimasa Pandemi Covid-19 - mariko, suhatri (El-kahfi | Jurnal Ekonomi Islam, 2021)
The main problem of this research is the Marketing Strategy used by BMT Al Makmur in increasing the number of Funding customers during the Covid-19 Pandemic. The purpose of this discussion is to find out and analyze the Marketing Strategy used by BMT Al Makmur in increasing the number of Funding customers during the Covid-19 Pandemic. The type of research that the author uses is field research with a qualitative descriptive approach. Data collection techniques are observation, interviews and documentation. From the research conducted, it was found that the marketing strategies carried out by BMT Al Makmur to increase the number of customers during the Covid-19 Pandemic were First Optimizing the roles and functions of marketing personnel, Second Optimizing Personal Selling Marketing Strategies (Personal Selling), Third Providing Service Excellence to customers, Fourth Build and establish active synergy with the government and institutions in the work area.